Demographic and temporal trends in out of hospital sudden cardiac death in Belfast. Issue 3 (6th June 2005) - Moore, M J; Glover, B M; McCann, C J; Cromie, N A; Ferguson, P; Catney, D C; Kee, F; Adgey, A A J
Abstract : Objective: To determine the epidemiology of out of hospital sudden cardiac death (OHSCD) in Belfast from 1 August 2003 to 31 July 2004. Design: Prospective examination of out of hospital cardiac arrests by using the Utstein style and necropsy reports. World Health Organization criteria were applied to determine the number of sudden cardiac deaths. Results: Of 300 OHSCDs, 197 (66%) in men, mean age (SD) 68 (14) years, 234 (78%) occurred at home. The emergency medical services (EMS) attended 279 (93%). Rhythm on EMS arrival was ventricular fibrillation (VF) in 75 (27%). The call to response interval (CRI) was mean (SD) 8 (3) minutes. Among patients attended by the EMS, 9.7% were resuscitated and 7.2% survived to leave hospital alive. The CRI for survivors was mean (SD) 5 (2) minutes and for non-survivors, 8 (3) minutes (p < 0.001). Ninety one (30%) OHSCDs were witnessed; of these 91 patients 48 (53%) had VF on EMS arrival. The survival rate for witnessed VF arrests was 20 of 48 (41.7%): all 20 survivors had VF as the presenting rhythm and CRI ⩽ 7 minutes. The European age standardised incidence for OHSCD was 122/100 000 (95% confidence interval 111 to 133) for men and 41/100 000 (95% confidence interval 36 to 46) for women. Conclusion: Despite a 37% reduction in heart attack mortality in Ireland over the past 20 years, the incidence of OHSCD in Belfast has not fallen. In this study, 78% of OHSCDs occurred at home.